Strategi Pembudayaan Akhlak al Karimah bagi Siswa: Studi di MAN Wonokromo Bantul Yogyakarta - Syamsul Huda (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This study aimed to: a. Identify the model of akhlaq al karimah culture building for students of MAN Wonokromo Bantul, b. to describe the results of akhlaq al karimah culture building for students of MAN Wonokromo Bantul and its implementation in daily life. This research is a descriptive-analytical study with a qualitative approach. The data were collected through observation, interview, and documentation. The data validity was checked through participation prolongation, observation persistence, and triangulation (of methods and sources). The data analysis technique involved the interactive model, including data collection, data reduction, data display, and data verification. The results showed that the model of akhlaq al karimah culture building for students of MAN Wonokromo included akhlaq al karimah culture building through learning, modeling, habit-forming, and praying. Meanwhile, the results of akhlaq al karimah culture building in this school included being religious, discipline, and hardworking as well as owning honesty and curiosity. It is recommended that the akhlaq al karimah culture building should be well planned, organized, controlled, and long-lasting, to produce students that have the spirit of faith, Islam, and good deeds according to the school vision and mission to create faithful, pious, noble, smart, independent, and fruitful students.